Limitations of routine MALDI-TOF mass spectrometric identification of Acinetobacter species and remedial actions - Šedo, Ondrej; Radolfová-Křížová, Lenka; Nemec, Alexandr; Zdráhal, Zbyněk (Journal of microbiological methods, 2018)
A set of 204 taxonomically well-defined strains belonging to 17 Acinetobacter spp., including 11 recently described species (A. albensis, A. bohemicus, A. colistiniresistens, A. courvalinii. A. dispersus, A. gandensis, A. modestus, A. proteolyticus, A. seifertii, A. variabilis, and A. vivianii) and six species of the so-called haemolytic clade (A. beijerinckii, A. gyllenbergii, A. haemolyticus, A. junii, A. parvus, and A. venetianus), were subjected to MALDI-TOF mass spectrometric profiling. The identification outputs were evaluated using the current version (8.0.0.0) of the commercially available Bruker Daltonics, Biotyper database, which does not contain reference entries for six of the species tested. Up to 29% of the strains were falsely identified as different Acinetobacter spp. present in the Biotyper database, resulting mostly from the close phylogenetic relationship of species of the haemolytic clade. To obtain more reliable identification, extending the commercial database showed only partial improvement, while the use of an alternative MALDI matrix solution (strongly acidified ferulic acid) allowed correct identification of nearly all problematic strains.
Keywords: Limit of Detection; limita detekce; BioTyper; Phylogeny; databáze genetické; Genes, Bacterial; RNA ribozomální 16S; infekce bakteriemi rodu Acinetobacter; Acinetobacter spp.; Acinetobacter; RNA, Ribosomal, 16S; MALDI-TOF MS; spektrometrie hmotnostní - ionizace laserem za účasti matrice; fylogeneze; bakteriální geny; Databases, Genetic; Bacterial Typing Techniques; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Bacteria profiling; techniky typizace bakterií; Acinetobacter Infections